A BIBLIOMETRIC ANALYSIS OF PROFESSIONAL LEARNING COMMUNITIES AND TEACHER PROFESSIONALISM IN GLOBAL EDUCATION RESEARCH - Sikri, Nursyahida; Ismail, Nor Hasimah; Ismail, Siti Noor (INTERNATIONAL JOURNAL OF EDUCATION, PSYCHOLOGY AND COUNSELLING (IJEPC), 2025)
This study presents a comprehensive bibliometric analysis of Professional Learning Communities (PLCs) and teacher professionalism within the context of global education research, aiming to map the intellectual structure, research trends, and collaborative networks that have emerged over the past decade. Despite the increasing recognition of PLCs as a critical mechanism for enhancing teacher competency, collaboration, and professional identity, limited systematic evidence exists on how this research field has evolved internationally. To address this gap, bibliometric techniques were applied using data retrieved from Scopus through advanced searching with the keywords “Professional Learning Community,” “collaborative learning community,” “Teacher,” and “educator,” yielding a final dataset of 473 documents. The methodology employed a four-stage process: data collection from Scopus, statistical and graphical trend analysis using Scopus Analyzer, data cleaning and harmonization with OpenRefine, and network visualization through VOSviewer. The analysis revealed significant growth in publications after 2015, with research output dominated by contributions from the United States, China, Australia, and the United Kingdom, indicating strong Western and Asian engagement in this domain. Co-authorship and co-occurrence mapping highlighted eight major thematic clusters, including teacher collaboration, professional identity development, instructional leadership, and student achievement outcomes, demonstrating the multidimensional scope of PLC-related research. Citation patterns further underscore the theoretical and practical significance of PLCs in shaping pedagogical practices and fostering sustainable professional growth among educators. By consolidating these findings, the study contributes to the body of knowledge by offering evidence-based insights into global research dynamics, identifying key knowledge hubs and gaps, and guiding future scholarship toward a more integrated and contextually relevant understanding of PLCs and teacher professionalism.